1997
DOI: 10.1074/jbc.272.34.20998
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid Is a Reducing Substrate and Not an Effective Inhibitor of Ascorbate Peroxidase

Abstract: This communication describes the interactions of salicylic acid (SA) with plant ascorbate peroxidase (APX).Contrary to a recent report (Durner, J., and Klessig, D. F. (1995) Proc. Natl. Acad. Sci. U. S. A. 92, 11312-11316) we show conclusively that ascorbate oxidation by APX is not inhibited by SA (10 mM), but that SA is a slow reducing substrate of this enzyme. The suggestion that SA-dependent inhibition of APX in planta may result in the elevation of H 2 O 2 levels, which in turn acts as a second messenger i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…However, recent reports have indicated that SA may not inhibit these activities during the HR (Kvaratskhelia et al, 1997;Tenhaken and Rubel, 1997). Our findings suggest that in addition to the possible inhibition of cAPX activity by SA, the expression of the cAPX protein is suppressed.…”
Section: Apx Suppression During Pcdmentioning
confidence: 43%
See 2 more Smart Citations
“…However, recent reports have indicated that SA may not inhibit these activities during the HR (Kvaratskhelia et al, 1997;Tenhaken and Rubel, 1997). Our findings suggest that in addition to the possible inhibition of cAPX activity by SA, the expression of the cAPX protein is suppressed.…”
Section: Apx Suppression During Pcdmentioning
confidence: 43%
“…Thus, no newly synthesized cAPX protein may replace the SA-inactivated cAPX molecules during pathogen-induced PCD. On the other hand, because SA may not inhibit the activity of APX (Kvaratskhelia et al, 1997), because it was found that H 2 O 2 application stimulated the production of SA (Leon et al, 1995), and because SA application in the absence of pathogen infection was found to act as a rather weak signal for the induction of defense mechanisms (Shirasu et al, 1997), it is possible that the suppression of cAPX expression acts before or independent of the accumulation of SA. It is also possible that the reduced capability of cells to remove H 2 O 2 together with the extracellular production of and H 2 O 2 induce the synthesis of SA and enable the rapid and efficient activation of defense mechanisms and PCD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that SA inhibits ascorbate peroxidase and catalase, two key enzymes for scavenging H 2 O 2 , by serving as an electron-donating substrate (Durner and Klessig, 1995), although SA was shown to be a better reducing substrate than an effective inhibitor (Kvaratskhelia et al, 1997). This role is supported by the redox deactivation mechanism by SA of the iron Fenton reaction centers (Cheng et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…APX is also an important defence enzyme, which protects plant cells from disease agents via systemic D. Bayram et al 2421 acquired resistance [61]. In this study, as the number of days increased, a marked increase was observed in the APX activity in the groups treated with quizalofop-p-ethyl, whereas a decrease was observed on the 10th and 15th days (Figure 3).…”
Section: Discussionmentioning
confidence: 47%